2016
DOI: 10.1371/journal.pone.0164352
|View full text |Cite
|
Sign up to set email alerts
|

Altered Expression of Human Smooth Muscle Myosin Phosphatase Targeting (MYPT) Isovariants with Pregnancy and Labor

Abstract: BackgroundMyosin light-chain phosphatase is a trimeric protein that hydrolyses phosphorylated myosin II light chains (MYLII) to cause relaxation in smooth muscle cells including those of the uterus. A major component of the phosphatase is the myosin targeting subunit (MYPT), which directs a catalytic subunit to dephosphorylate MYLII. There are 5 main MYPT family members (MYPT1 (PPP1R12A), MYPT2 (PPP1R12B), MYPT3 (PPP1R16A), myosin binding subunit 85 MBS85 (PPP1R12C) and TIMAP (TGF-beta-inhibited membrane-assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 26 publications
0
11
0
1
Order By: Relevance
“…Protein phosphatase 1 regulatory subunit 12B (PPP1R12B) may be involved with insulin signaling (Pham et al, 2012). This gene is associated with smooth muscle contractibility and regulation of uterine cell hypertrophy in the early stages of gestation (Lartey et al, 2016). Ryu et al (2016) found that PPP1R12B participates in protein phosphorylation, which may influence reproduction in humans.…”
Section: Genes Associated With the Number Of Antral Folliclesmentioning
confidence: 99%
“…Protein phosphatase 1 regulatory subunit 12B (PPP1R12B) may be involved with insulin signaling (Pham et al, 2012). This gene is associated with smooth muscle contractibility and regulation of uterine cell hypertrophy in the early stages of gestation (Lartey et al, 2016). Ryu et al (2016) found that PPP1R12B participates in protein phosphorylation, which may influence reproduction in humans.…”
Section: Genes Associated With the Number Of Antral Folliclesmentioning
confidence: 99%
“…PPP1R12A, located 9.7 kb downstream of rs17005877, is involved in the expression of light-chain myosin phosphatase. This protein belongs to the family of myosin targeting subunit (MYPT), which is involved in the regulation of light chain myosin phosphatase recently implicated in the aberrant contractility associated with atherosclerosis [40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…PIK3CA was found participated in the process of gland development and epithelial cell invasiveness, which are of great importance in the pathology of adenomyosis [ 35 ] [ 36 ]. PPP1R12C and PPP1R12B are the main members of myosin-targeting subunit (MYPT), which is a major component of the phosphatase and a crucial determinant of function of smooth muscle cells [ 37 ]. In the present study, the low expression levels of PPP1R12C and PPP1R12B were partly related to the myometrium injury in adenomyosis, and anti-NGF therapy might be advantageous for repair of myometrial defect.…”
Section: Discussionmentioning
confidence: 99%